ANALYSIS OF TEACHERS’ MANAGEMENT AND INSTRUCTIONAL TALK IN ENGLISH FOREIGN LANGUAGE (EFL) CLASSROOM AT SMA NEGERI 1 BOMBANA - Roslina (Getsempena English Education Journal, 2021)
This study aims were to determine the context of teacher management and instructional talks in senior high schools, especially in Senior High Schools of 1 Bombana and the frequency of use of teachers' native language (NL) and target language (TL). The study subjects were two Indonesian English teachers. The descriptive qualitative method was used to obtain and analyze data. Our study results showed four contexts of utterance related to management talk while three contexts were related to the instructional talk. Teachers prefer to use the native language than the target language in either management talk term or instructional talk term. The frequency of using the native language was much higher both in management and instructional talk. It indicated by 86.9% average used in management talk, while 77.1% in the instructional talk. In addition, the reason for the domination of the native language was to reach the effectiveness of learning in EFL classes. However, it was also implied that the teacher's competence to use English in the classroom was inadequate.